Strategic Management of Utilisation of Zakāh Funds in Improving Mustaḥiq's Welfare in The Productive Bojonegoro Programme at BAZNAS of Bojonegoro Regency - Rahayu, Fitri Amalia; Rahman, Taufiqur; Ariffin, Mohd Faizal Noor bin (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study aims to explore the strategic management of zakāh fund utilization within the Productive Bojonegoro Programme at BAZNAS of Bojonegoro Regency, Indonesia, and its effectiveness in improving the economic welfare of mustaḥiq (zakāh recipients). Employing a qualitative-descriptive method through direct observation, interviews, and document analysis, the research reveals that zakāh funds channeled into productive sectors—such as small business tools, livestock assistance, and microenterprise training—can transform mustaḥiq into self-sufficient economic agents. The findings demonstrate that effective zakāh strategies involve comprehensive planning, rigorous standard operating procedures (SOPs), targeted recruitment, and ongoing monitoring to ensure sustainable impact. This study advances the discourse on Islamic social finance by presenting a replicable strategic management framework that links zakāh disbursement to long-term poverty alleviation. It also provides empirical evidence supporting the shift from consumptive to productive zakāh models in localized Muslim-majority settings. Future studies may expand upon this model by applying comparative approaches across other regions or by assessing the long-term transition of mustaḥiq into muzakkī (zakāh payers), thereby contributing to the theory and practice of Islamic economic empowerment.